Analysing the effects of funny and viral contents on brand awareness creation pertaining to SA retail banking’s online consumers - Mandhlazi, L. (FMLIC - Conference Proceedings, 2024)
The purpose of this study was to determine the effects of funny and viral content on brand awareness creation. Three objectives were derived from this study: (1) to analyse the relationship between funny content and user engagement; (2) to determine the relationship between viral content and user engagement; and (3) to examine the relationship between user engagement and brand awareness creation. A quantitative method was used to conduct the study. The study revealed that funny content has a significant positive relationship with user engagement. Furthermore, the study found that viral content did not have a relationship with user engagement. However, user engagement was found to have no relationship with brand awareness creation. Practical implications: The brand managers of the local retail banks would be able to effectively design humorous contents that are trending across social media platforms. Brand managers would further be able to develop robust strategies that can encourage consumers to become content creators, as opposed to be consumers of content across social media platforms. Study contributions: The study would add a new theoretical and practical perspective to the body of knowledge within the South African banking industry pertaining to social media banking context.
Keywords: Funny; Viral; Brand; Online; South Africa